Variety of Forms and Kinds of Independent Work of Students- Philologists under the Conditions of Credit-Module System of Educational Process Organization - Bondar, Liliya (Pedagogical Discourse, 2013)
The ways of optimizing the educational process in high school through the diversity of forms and kinds of independent work of the students of philological faculty in credit-module system of organizing of educational process are identified and the role of independent work in improving the effectiveness of training teachers is revealed in this article. Internal and external factors affecting the nature, intensity and productivity of students’ independent work are identified, characteristics for steps specified with methodology of activating the process of self-education of the students are given here, the main criteria of readiness of university students to the organization of independent work are identified in the article as well.